ANALISIS KEPUTUSAN WANITA MENIKAH UNTUK BEKERJA (STUDI KASUS KOTA SURAKARTA JAWA TENGAH) - Tofelisa Sipayung, Isty Laura; Waridin, Waridin (Diponegoro Journal of Economics, 2013)
This study aimed to analyze the influence of educational variables, husbands wages, number of dependents, and age on the decision of married women to work, with a case study of Surakarta.In determining the location of the research, this study using the